2018
DOI: 10.1155/2018/8126127
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Adaptive Synchronization for Stochastic Neutral-Type Memristive Neural Networks with Mixed Time-Varying Delays

Abstract: Linear feedback control and adaptive feedback control are proposed to achieve the synchronization of stochastic neutral-type memristive neural networks with mixed time-varying delays. By applying the stochastic differential inclusions theory, Lyapunov functional, and linear matrix inequalities method, we obtain some new adaptive synchronization criteria. A numerical example is given to illustrate the effectiveness of our results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…The constant delay is constant and discrete, which means that the effect of the state is delayed by a fixed value on the system. It can be observed that most of the literature works mainly focus on three simple cases containing constant delays, distributed delays, and time-varying delays (see [20][21][22]). In fact, mixed delays have been considered to be more efficient in modeling neural network systems because these simple delays are often not feasible when neural network systems become more complex.…”
Section: Introductionmentioning
confidence: 99%
“…The constant delay is constant and discrete, which means that the effect of the state is delayed by a fixed value on the system. It can be observed that most of the literature works mainly focus on three simple cases containing constant delays, distributed delays, and time-varying delays (see [20][21][22]). In fact, mixed delays have been considered to be more efficient in modeling neural network systems because these simple delays are often not feasible when neural network systems become more complex.…”
Section: Introductionmentioning
confidence: 99%
“…Dissipative system theory provides a framework for the design and analysis of control systems based on energy-related considerations [17]. At present, although there are some studies on the dissipativity of neural networks [18][19][20], most of them are focusing on the synchronization of neural networks [21][22][23][24]. For the dissipativity analysis of neural networks, it is essential to find global exponentially attracting sets.…”
Section: Introductionmentioning
confidence: 99%